Penerapan Algoritma Sequential Search Pada Sistem Informasi Pendataan Peralatan Outdoor Di UKM Kapal Baja - Irsya Fadillah; Warta, Joni (Journal of Informatic and Information Security, 2023)
This research designs and implements a website-based goods inventory application using the Sequential Search (SS) algorithm in Steel Ship UKM. The aim is to overcome problems that often occur in the process of borrowing and returning goods, frequent loss of goods, and to be more efficient in recording outdoor equipment. Implementation of this sequential search algorithm to search for items based on the date the user borrowed and returned the item. This evaluation was carried out on the logistics bureau division in recording goods, borrowing and returning goods in real world conditions within the organization and externally. The results of this research show that the application Website-based inventory of goods that utilizes the sequential search (SS) algorithm can provide an effective solution for recording outdoor equipment and borrowing and returning outdoor equipment transactions both internally and externally at UKM Kapal Baja.